0695 Sleepwell24, A Smartphone Application To Promote PAP Therapy Adherence: Feasibility And Acceptability. (27th May 2020) - Petrov, M E; Hasanaj, K; Hoffmann, C M; Epstein, D R; Krahn, L; Park, J G; Hollingshead, K; Yu, T; St. Louis, E K; Morgenthaler, T I; Buman, M P
Abstract: Introduction: We aimed to test the feasibility and acceptability of SleepWell24, a multicomponent, smartphone-delivered intervention to increase positive airway pressure (PAP) adherence among newly diagnosed OSA patients. Methods: SleepWell24 targets PAP adherence along with other health behaviors through education, trouble-shooting, goal-setting, and near real-time biofeedback of PAP machine use, and sleep and physical activity levels (via Fitbit integration), and other chronic disease self-management components. Patients with a first-time diagnosis of OSA (AHI≥5) and prescribed PAP therapy were enrolled from the Centers for Sleep Medicine at Mayo Clinic in Rochester, MN and Phoenix, AZ. Patients were randomized to SleepWell24 or usual care (UC) and assessed for PAP use over 60 consecutive nights. UC patients received a Fitbit monitor to control for non-specific intervention effects related to the introduction of a new personal technology. Feasibility was assessed with recruitment and retention rates and acceptability was assessed post-intervention with the validated, 8-item Treatment Evaluation Questionnaire (TEQ; range:0-4). ANCOVA models, adjusting for age, sex, and AHI severity, compared intervention arms on acceptability ratings. Results: OSA patients were consented and randomized (N=111). Before the intervention began 4 participants withdrew, 12 were lost to follow-up, and 5 could not start the trial due to durable medical equipment (DME) vendor barriers. Ninety OSA patients (n=41 SleepWell24, n=49 UC; age M ± SD =57.2±12.2; 44.4% female, 61.1% AHI≥15) started the intervention, with 2 participants withdrawing, 1 becoming deceased (unrelated to treatment) and 7 with missing PAP data due to DME vendor barriers. There was no significant between-groups differences on post-treatment acceptability ( SleepWell24 M ± SD =2.7±1.1 vs. UC M ± SD= 3.1±0.9, F [1, 73]=2.3, p =0.11), and 77% of SleepWell24 participants found the app to be moderately to totally acceptable. Conclusion: Overall, SleepWell24 was found to be feasible for delivery in two large clinical sleep medicine centers, and patients found the app to be acceptable. A number of challenges in trial delivery were encountered that have implications for scaled-up efficacy testing: (a) partnerships with DME vendors for near real-time PAP data integration; (b) alignment with clinical practice (i.e., referral, medical record integration); and (c) patient engagement. Support: National Institute of Nursing Research / National Institutes of Health: R21NR016046